S(N)2 ring opening of beta-lactones: An alternative to catalytic asymmetric conjugate additions - Nelson, SG; Wan, ZH; Stan, MA (Journal of organic chemistry, 2002)
Merging catalytic asymmetric acyl halide-aldehyde cyclocondensation (AAC) reactions with ensuing Grignard-mediated ring opening of the derived enantiomerically enriched beta-lactones is presented as a generally useful asymmetric synthesis of beta-disubstituted carboxylic acids. Enantiomerically enriched beta-lactones are subject to efficient S(N)2 ring opening with a variety of copper-modified alkyl Grignard reagents, including highly branched nucleophiles. Considerable structural variation in the lactone electrophile is also tolerated. Phenyl- and vinyl-derived organometallics are not efficient nucleophiles for the ring-opening reactions.